2013
DOI: 10.3168/jds.2012-5975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Origanum vulgare L. leaves on rumen fermentation, production, and milk fatty acid composition in lactating dairy cows

Abstract: This experiment investigated the effects of dietary supplementation of Origanum vulgare L. leaf material (OR) on rumen fermentation, production, and milk fatty acid composition in dairy cows. The experimental design was a replicated 4 × 4 Latin square with 8 rumen-cannulated Holstein cows and 20-d experimental periods. Treatments were control (no OR supplementation), 250 g/cow per day OR (LOR), 500 g/d OR (MOR), and 750 g/d OR (HOR). Oregano supplementation had no effect on rumen pH, volatile fatty acid concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
94
5
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 56 publications
18
94
5
6
Order By: Relevance
“…Lin et al [36] observed a NH3 inhibition with a mixture of EOs composed of clove, oregano, cinnamon and lemon in sheep (1 g/day). Contrasting results on in vivo NH3 production were found by Hristov et al [31] and Tekippe et al [32] by feeding dairy cows with a supplementation of oregano leaves. However, as confirmed by the present study, the positive effects of EOs on CH4 and NH3 production are frequently associated to negative effects on feed digestibility, especially at the highest doses [28,37,38].…”
Section: Controlmentioning
confidence: 54%
See 1 more Smart Citation
“…Lin et al [36] observed a NH3 inhibition with a mixture of EOs composed of clove, oregano, cinnamon and lemon in sheep (1 g/day). Contrasting results on in vivo NH3 production were found by Hristov et al [31] and Tekippe et al [32] by feeding dairy cows with a supplementation of oregano leaves. However, as confirmed by the present study, the positive effects of EOs on CH4 and NH3 production are frequently associated to negative effects on feed digestibility, especially at the highest doses [28,37,38].…”
Section: Controlmentioning
confidence: 54%
“…Some in vivo tests confirmed the potential of these plants and their extracts in CH4 mitigation. Hristov et al [31] demonstrated a CH4 production reduction (−16.5, −11.7 and −13.6 g of methane per kg of DM intake) by three different doses of dietary oregano leaves (respectively 250, 500 and 750 g/animal per day) in dairy cows. Tekippe et al [32] found similar results in dairy cows fed by oregano leaves at a 500 g/d rate (40% reduction in methane production).…”
Section: Effects On Gas Production and Feed Degradabilitymentioning
confidence: 99%
“…The inclusion of spices, especially those containing essential oils, into the diet of ruminants is increasing due to their effects on ruminal fermentation [5, 6] and animal health [10, 24, 25], although there are reduced evidences of spices' effects improving animal performance [26]. In nonruminants, essential oils have been used in a wide scale due to their potential as replacement of antibiotics [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Benchaar et al (2007) found on dairy cattle that the profile of milk fatty acids of cows was not influenced by the supplementation with 750 mg per day of a mixture of EO compounds. Similarly, Hristov et al (2013) did not observe variations in milk fatty acids when supplementing the diet of lactating cows with three dosages of Origanum vulgare leaves.…”
Section: Essential Oilsmentioning
confidence: 99%